The Effect of Therapeutic Low-Frequency Ultrasound applied to Myofascial Trigger Points: A Pilot Pre-Post Design Study - Michal Elboim Gabyzon; Amit Drat; Leonid Kalichman (Ital Publication, 2021)
Ultrasound at a frequency of 1 or 3 MHz is frequently used to treat various musculoskeletal conditions, but research on ultrasound operating at 38-50 kHz frequencies (US-KHz) is lacking. Study aimed to evaluate the short-term effect of US-KHz on pain pressure threshold (PPT), ankle dorsiflexion range of motion (ROM), and motor performance (the Side Hop Test) in subjects with a myofascial trigger point (TrP) in the calf muscle. US-KHz was applied to the area of the palpable TrP in the calf muscle for 10 minutes (continuous pulse, transducer head size 19.6 cm2, power 0.75-1.25 w/cm2) in twenty volunteers (18-45 years old). Significant improvements (p<0.001) were noted in the Side Hop Test 24 hours after the intervention. ROM improved significantly after 5 minutes with changes maintained 24 hours later. No change was found in the PPT. This pilot study presents preliminary evidence of the efficacy of US-KHz in treating TrPs.   Doi: 10.28991/SciMedJ-2021-0303-5 Full Text: PDF